A Single-Center Retrospective Analysis of Local and Distant Relapse of Breast Cancer Following Immediate Breast Reconstruction According to Molecular Subtypes - Han, Chunyong; Zhang, Xuehui; Sun, Jingyan; Liu, Jing; He, Shanshan; Yin, Jian (Frontiers in Oncology, 2022)
Purpose: Concerns have been raised about the oncologic safety of immediate breast reconstruction following mastectomy for breast cancer. This study aimed to evaluate locoregional recurrence and distant metastasis of breast cancer according to its molecular subtype between patients underwent mastectomy alone and immediate breast reconstruction after mastectomy. Methods: In this retrospective cohort study, consecutive breast cancer patients treated by the single senior surgeon (Zhang XH) between Feb. 2010 and Dec. 2014 were eligible. In total, 389 consecutive patients were included, 295 patients underwent mastectomy alone and 94 patients underwent mastectomy with immediate breast reconstruction (IBR). Data were retrospectively collected and analyzed for locoregional recurrence and distant metastasis stratified by molecular subtypes. Results: With a median follow-up of 73 and 87.5 months, 1.69% of patients in the mastectomy alone group developed locoregional recurrence (LRR) compared to 0% in the reconstruction group (p=0.342), the total incidence of distant metastases (DM) was 11.52% in patients who received mastectomy alone and 7.44% in patients who received postmastectomy IBR (p =0.262), respectively. The cumulative incidence of LRR was 2.1% versus 0% for luminal A; 0% versus 0% for luminal B; 0% versus 0% for HER2 enriched; and 4.5% versus 0% for triple negative in the mastectomy alone group compared to the postmastectomy IBR group. The cumulative incidence of DM was 15.5% versus 5.7% for luminal A; 10% versus 8.7% for luminal B; 17.3% versus 0% for HER2 enriched; and 6.8% versus 7.1% for triple negative in the mastectomy alone group compared to the postmastectomy IBR group. On multivariable Cox regression analysis, lymph node metastasis was associated with increased risk of DM in mastectomy alone group (p=0.03) and neoadjuvant chemotherapy was associated with increased risk of DM in postmastectomy IBR group (p=0.021). Conclusion: This study suggests that immediate breast reconstruction does not have a negative impact on the locoregional recurrence and distant metastasis of breast cancer according to molecular subtypes.